From Poor Law to community care : the development of welfare services for elderly people 1939-1971 - Means, Robin (Policy Press, 1998)
Based on extensive research on primary sources and interviews with key actors, this book explores the changing perceptions of the needs of elderly people. It considers the extent to which they have been a priority for resources and looks at the possibilities of policy that combines respect for elderly people with an avoidance of the exploitation of relatives.